Minimum Wage Analysis Using a Pre-Committed Research Design: Evidence through 2018 - Jeffrey Clemens; Michael R. Strain (Institute of Labor Economics (IZA), 2020)
This paper presents results from the fourth year of a multi-year, pre-committed research design for analyzing recent minimum wage changes. Using ACS and CPS data through 2018, we find that relatively large minimum wage increases reduced employment among low-skilled individuals by roughly 2.5 percentage points. The effects of smaller statutory increases and inflation-indexed increases vary across data sets and specifications, but are generally not distinguishable from zero. The relationship between minimum wage increases and employment is quite strongly negative in states that began enacting substantial increases between 2013 and 2015. In states that began enacting increases later in the economic expansion, estimates are more variable and tend towards zero.
Keywords: J08; J23; J38; 330; minimum wages; employment; pre-commitment